2019
DOI: 10.1017/s0714980818000582
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aerobic Exercise on White Matter Hyperintensity Progression May Vary by Sex

Abstract: RÉSUMÉCette étude a exploré l’efficacité de l’entraînement aérobie (EA) pour atténuer la progression de l’hyperintensité de la matière blanche (HMB) et les différences liées au sexe pour cette intervention. Un essai contrôlé randomisé a été mené pour évaluer l’effet de l’EA sur la cognition de personnes ayant un déficit cognitif d’origine vasculaire. Les participants ont été répartis aléatoirement entre deux groupes : 6 mois d’EA ou soins standards (groupe contrôle). Dans un sous-groupe de participants, l’imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
0
19
1
Order By: Relevance
“…Another study did not note either an improvement in memory or sex moderation in improvement with a brief bout of moderate intensity exercise [32]. Lastly, an intervention study assessing the efficacy of a 6-month aerobic training in mitigating white matter hyperintensity progression in older adults with vascular cognitive impairment found that men who had completed the aerobic training intervention, in comparison to the women completing the same intervention, had significantly less white matter hyperintensity progression [13]. Thus, sex differences have been noted, but few intervention studies have specifically reported sex differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study did not note either an improvement in memory or sex moderation in improvement with a brief bout of moderate intensity exercise [32]. Lastly, an intervention study assessing the efficacy of a 6-month aerobic training in mitigating white matter hyperintensity progression in older adults with vascular cognitive impairment found that men who had completed the aerobic training intervention, in comparison to the women completing the same intervention, had significantly less white matter hyperintensity progression [13]. Thus, sex differences have been noted, but few intervention studies have specifically reported sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…The planned analyses for our trial did not incorporate sex moderation. Few randomized controlled trials have addressed the potential moderation of exercise effects by sex despite the fact that several observational and intervention studies have found sex differences in the cognitive benefit from physical exercise or physical activity [7,8,9,10,11,12,13]. Two meta-analyses [3,14] suggested that women might benefit from aerobic exercise more than men, but these analyses were not based on direct comparison of exercise benefit by sex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, these factors can also be classified as endogenous factors (factors attributable to the individual such as sex or genotypes) and exogenous factors (factors attributable to external inputs, e.g., generated by exercise prescription) (Sparks, 2017). Currently, the roles of non-modifiable (endogenous) factors such as sex (Barha et al, 2017a, b, 2019; Barha and Liu-Ambrose, 2018; Cobbold, 2018; Loprinzi and Frith, 2018; Dao et al, 2019) and genotypes (Booth and Laye, 2010; Timmons et al, 2010; Timmons, 2011; Bouchard, 2012, 2019; Mann et al, 2014; Bouchard et al, 2015; Jones et al, 2016; Pickering and Kiely, 2017a,b,c, 2018a; Del Coso et al, 2018) are investigated most. Among these factors, it has been shown that a considerable amount (approximately up to half of the variance) of the interindividual heterogeneity in physical outcomes (Bouchard and Rankinen, 2001; Timmons et al, 2010; Davidsen et al, 2011; Timmons, 2011; Bouchard, 2012; Wilson et al, 2019), cognitive outcomes (McClearn, 1997; Goldberg and Weinberger, 2004; Blokland et al, 2008; Erickson et al, 2008; Friedman et al, 2008; Canivet et al, 2015, 2017), and brain structure outcomes (Thompson et al, 2001; Toga and Thompson, 2005; Bueller et al, 2006) are explained by genetics.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve the above-mentioned goal will require more information and understanding regarding the mechanisms involved in responsiveness to exercise and better information regarding factors that modulate such responsiveness. There is clear evidence that sex can play a role in responsiveness to exercise at the level of the brain, with females responding more than males (reviewed in Barha et al, 2017Barha et al, , 2019Dao et al, 2019). This is an interesting response pattern since most Alzheimer patients are female.…”
mentioning
confidence: 99%